ASUHAN KEBIDANANIBU BERSALIN PADA NY. E UMUR 34 TAHUN G2 P1 A0 KALA I DENGAN FOKUS INTERVENSI PEMBERIAN AROMA TERAPI LEMON UNTUK MENURUNKAN NYERI DI TPMB SRI ENDANG KISNAWATI - Dela Putri Arumsari; Sri Untari; Laily Himawati (The Shine Cahaya Dunia Kebidanan, 2023)
Background; According to data from the Ministry of Health of the Republic of Indonesia (Kemenkes RI) in 2019, the number of maternity mothers was recorded as 5 050 637 people and the number of births in Indonesia is estimated to increase by 20% According to the Indonesian health profile in 2018 the maternal mortality rate (MMR) in Indonesia reached 305 per 100 000 live births in 2015, this has decreased compared to 2012 which was 359 per 100,000 live births and the target. decrease in mortality in 2030 by 131 per 100 000 live births (Kemenkes RI, 2019). Method; The research design that the researcher used was a case study research design. The type of research is a descriptive case study using participatory observation method The subjects in this study were mothers during the maternity phase active when I. Result; The results showed that Mrs. F's diagnosis was pain discomfort. Evaluation of the implementation of lemon aromatherapy in Mrs. E's case with pain at the time of it. There was a reduction in the pain scale from 7 (very severe) to 6 (severe). Conclusion; Problems of pain and discomfort in active phase maternity women when 1 Mrs E has been resolved.